Botulinum toxin A alleviates orofacial nociception induced by orthodontic tooth movement through nociceptin/orphanin-FQ pathway in rats. (September 2020) - Lyu, Jiahong; Wen, Jing; Guo, Rui; Zhu, Yafen; Liang, Hengyan; Gao, Meiya; Wang, Hang; Lai, Wenli; Long, Hu
Highlights: Periodontal injection of BoNT/A can alleviate orofacial nociception. BoNT/A can promote the expression of N/OFQ in trigeminal ganglion. UFP-101 can completely block BoNT/A's antinociceptive effect. BoNT/A alleviates orofacial nociception induced by orthodontic tooth movement through N/OFQ signaling. Abstract: Objectives: To investigate the effect and mechanism of botulinum neurotoxin type A (BoNT/A) in the modulation of orofacial nociception induced by orthodontic tooth movement in rats. Methods: An orofacial nociception model was established in male Sprague-Dawley rats by ligating closed-coil springs between incisors and ipsilateral molars. There were two group sets of animals. For the first group set, 120 rats were randomly divided into four groups: no-force group (n = 30), force + saline group (n = 30), force + low dose BoNT/A group (1U/6 μL, n = 30), and force + high dose BoNT/A group (1U/6 μL, n = 30). BoNT/A and saline were injected into periodontal ligament to explore the nociceptive effect of BoNT/A. Ipsilateral trigeminal ganglia (TG) were harvested for detecting the expression levels of nociceptin/orphanin-FQ (N/OFQ). For the second group set, 36 rats were randomly divided into three force groups: BoNT/A + saline group (n = 12), BoNT/A + UFP-101 group (n = 12), and saline + UFP-101 group (n = 12). A potent N/OFQ receptor (NOP) antagonist (UFP-101) was used to examine the role of N/OFQ in BoNT/A-induced antinociception. Tooth-movement nociception level of all groups was evaluated by bite force and rat grimace scale (RGS) at baseline, day 1, day 3, day 5, day 7, day 14. Results: The behavioral assessments showed the orofacial nociception level in the force + low dose BoNT/A group and force + high dose BoNT/A group were lower than that in the force + saline group. No significant difference was observed in orofacial nociception among no-force group, force + low dose and force + high dose group. The expression levels of N/OFQ in TG were elevated from day 1 and maintained a high level, presenting in descending order among the force + high dose, force + low dose, force + saline and no-force group, respectively. The nociception level of the BoNT/A + UFP-101 group was higher than that of the BoNT/A + saline group. No significant difference was observed between the BoNT/A + UFP-101 group and the saline + UFP-101 group. Conclusions: BoNT/A can exert an antinociceptive effect on orofacial nociception induced by tooth movement by stimulating the expression of N/OFQ in TG.